Effect of Foliar Application of Boron on the Yield And Quality of Potato (Bangladesh Journal of Agricultural Research, 2022)
Foliar application of boron on the yield and storability of potato was evaluated at Breeder Seed Production Centre, Debiganj during two consecutive years 2013-14 and 2014-15. Six different concentration of boron such as: 0 ppm B (T1), 70 ppm B (T2), 140 ppm B (T3), 210 ppm B (T4), 280 ppm B (T5) and 350 ppm B (T6) were tested. The maximum yield 35.9 and 35.3 t ha-1 in 2013-14 and 2014-15, respectively was found when plants treated with 210 ppm B as foliar application (T4). The highest dry matter content of tuber was obtained from T4. T4 (210 ppm B) also showed the minimum rottage loss of tuber. The highest gross margin and marginal benefit cost ratio were recorded in the same treatment. Foliar application of 210 ppm B can be recommended for economically potato production in Tista Meander Floodplain Soil.Bangladesh J. Agril. Res. 45(2): 125-135, June 2020